Selection and Characterization of ssDNA Aptamers Targeting Largemouth Bass Virus Infected Cells With Antiviral Activities - Yu, Qing; Li, Mengmeng; Liu, Mingzhu; Huang, Shuaishuai; Wang, Gaoxue; Wang, Taixia; Li, Pengfei (Frontiers in Microbiology, 2021)
Largemouth bass virus (LMBV) is one of the most devastating viral pathogens in farmed Largemouth bass. Aptamers are novel molecule probes and have been widely applied in the field of efficient therapeutic and diagnostic agents development. LMBV-infected fathead minnow cells (LMBV-FHM) served as target cells in this study, and three DNA aptamers (LBVA1, LBVA2, and LBVA3) were generated against target cells by SELEX technology. The selected aptamers could specifically bind to LMBV-FHM cells, with rather high calculated dissociation constants (Kd) of 890.09, 517.22, and 249.31 nM for aptamers LBVA1, LBVA2, and LBVA3, respectively. Three aptamers displayed efficient antiviral activities in vitro. It indicates that the selected aptamers have great potentials in developing efficient anti-viruses treatments. The targets of aptamers LBVA1, LBVA2, and LBVA3 could be membrane proteins on host cells. The targets of aptamers (LBVA1, LBVA2, and LBVA3) come out on the cells surface at 8, 10, 8 h post-infection. As novel molecular probes for accurate recognition, aptamer LBVA3 could detect LMBV infection in vitro and in vivo, it indicates that the selected aptamers could be applied in the development of rapid detective technologies, which are characterized by high sensitivity, accuracy, and easy operation.